STRATEGI KOMUNIKASI DINAS PARIWISATA PEMUDA DAN OLAHRAGA (DISPARPORA) DALAM MENARIK MINAT PENGUNJUNG FESTIVAL BOTUANG DI KOTA PAYAKUMBUH - Alqorni, Rahmat Wais; Salam, Noor Efni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The Botuang Festival is an annual event held in Payakumbuh City, West Sumatra, with the aim of introducing the city's culture and tourism to the wider public. This study aims to examine the communication strategies implemented by the Department of Tourism, Youth and Sports of Payakumbuh City in attracting visitors. This type of research is qualitative descriptive research, data collection techniques are carried out by interviews, observation and documentation. The data source uses 8 informants and resource persons consisting of the Head of the Destination Division of Disparpora, Sub. Coordinator of Tourism Promotion in the Tourism Marketing Division of Disparpora, Volunteers who work together with the Department of Tourism, Youth and Sports of Payakumbuh City, the Media Team @sudutpayakumbuh who is the media partner of the Botuang Festival in Payakumbuh City, Visitors who attended the Botuang Festival in Payakumbuh City, Visitors who did not attend the Botuang Festival in Payakumbuh City but knew that the festival was being held were selected using a purposive technique. The results of this study indicate that the success of the communication strategy used by the Payakumbuh City Disparpora in attracting visitors' interest in the Payakumbuh Botuang Festival event began with planning that was prepared as optimally as possible by considering visitor satisfaction both with the appearance and also the conduciveness of the event provided by the Disparpora.